2008
DOI: 10.1016/j.materresbull.2007.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and physical properties of Mg6Cu16Si7-type M6Ni16Si7, for M=Mg, Sc, Ti, Nb, and Ta

Abstract: Five compounds were investigated for magnetic character and superconductivity, all with non-magnetic nickel and band structures containing flat bands and steep bands.The syntheses and crystal structures, refined by powder X-ray diffraction, are reported for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…To obtain the magnetic contribution to the heat capacity of Mn 6 Ni 16 Si 7 one needs to subtract that of a suitable lattice match, normally a paramagnetic iso-structural compound. 38 A previous study of the magnetic properties of Ti 6 Ni 16 Si 7 showed a Pauli paramagnetic like behaviour, 25 which was also observed in our measurements of magnetic susceptibility of the compound under an applied magnetic field of 1000 Oe (SI-3).…”
Section: Magnetic Susceptibilitysupporting
confidence: 87%
See 2 more Smart Citations
“…To obtain the magnetic contribution to the heat capacity of Mn 6 Ni 16 Si 7 one needs to subtract that of a suitable lattice match, normally a paramagnetic iso-structural compound. 38 A previous study of the magnetic properties of Ti 6 Ni 16 Si 7 showed a Pauli paramagnetic like behaviour, 25 which was also observed in our measurements of magnetic susceptibility of the compound under an applied magnetic field of 1000 Oe (SI-3).…”
Section: Magnetic Susceptibilitysupporting
confidence: 87%
“…However, the heat capacity as a function of temperature showed a cusp at 140 K for Ti 6 Ni 16 Si 7 (closed circles in Fig. 3a), which is an indication of a phase transition, nevertheless unexpected, given the data of Holman et al 25 and our magnetic measurements. The origin of this anomaly is unclear at present, but apart from this feature, Ti 6 Ni 16 Si 7 appeared to be a reasonable lattice match.…”
Section: Heat Capacity Measurementsupporting
confidence: 57%
See 1 more Smart Citation
“…As was mentioned by Holman et al . (2008) for synthetic phases with the Mg 6 Ni 16 Si 7 structure type, such structures can be described conveniently in terms of large intermetallic polyhedra. The nipalarsite structure contains a cluster of eight Ni atoms formed from two interpenetrating Ni 4 tetrahedra (Fig.…”
Section: Description Of the Crystal Structurementioning
confidence: 99%
“…NiTi is a known shape memory alloy (SMA) [15,16,17]. The Ti 6 Ni 16 Si 7 phase, also called G-phase, is a known precipitate in steels and was investigated as a candidate for superconductivity [18,19]. Ti 2 Ni has been tested as a hydrogen storage material [20] as well as for its high-temperature wear properties [21].…”
Section: Introductionmentioning
confidence: 99%